Optimal dosing of dihydroartemisinin-piperaquine for seasonal malaria chemoprevention in young children - Chotsiri, P; Zongo, I; Milligan, P; Compaore, Y; Anyirékun Fabrice, S; Chandramohan, D; Hanpithakpong, W; Nosten, F; Greenwood, B; Rosenthal, P; White, N; Ouédraogo, J; et al. (Springer Nature, 2019)
Young children are the population most severely affected by Plasmodium falciparum malaria. Seasonal malaria chemoprevention (SMC) with amodiaquine and sulfadoxine-pyrimethamine provides substantial benefit to this vulnerable population, but resistance to the drugs will develop. Here, we evaluate the use of dihydroartemisinin-piperaquine as an alternative regimen in 179 children (aged 2.33–58.1 months). Allometrically scaled body weight on pharmacokinetic parameters of piperaquine result in lower drug exposures in small children after a standard mg per kg dosage. A covariate-free sigmoidal EMAX-model describes the interval to malaria re-infections satisfactorily. Population-based simulations suggest that small children would benefit from a higher dosage according to the WHO 2015 guideline. Increasing the dihydroartemisinin-piperaquine dosage and extending the dose schedule to four monthly doses result in a predicted relative reduction in malaria incidence of up to 58% during the high transmission season. The higher and extended dosing schedule to cover the high transmission period for SMC could improve the preventive efficacy substantially.